2021
DOI: 10.1111/jth.15262
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19 patients often show high‐titer non‐platelet‐activating anti‐PF4/heparin IgG antibodies

Abstract: Background Heparin‐induced thrombocytopenia (HIT) is a severe adverse reaction to heparin caused by heparin‐dependent, platelet activating anti‐platelet factor 4 (PF4)/heparin antibodies. Heparin is a cornerstone of treatment in critically ill COVID‐19 patients. HIT antibodies can be detected by antigen tests and functional tests. Often strong reactivity in the antigen test is used as surrogate marker for the presence of clinically relevant, platelet activating antibodies. We observed an unexpecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0
13

Year Published

2021
2021
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(73 citation statements)
references
References 26 publications
2
58
0
13
Order By: Relevance
“…In addition, in a previously healthy 56-year-old man with persistent neurological disorders, including short-duration epileptic seizures, and deep depression almost six months after COVID-19, CNS MRI revealed numerous hyperintense focal areas in the periventricular and subcortical white matter and in semioval centers, compatible with gliotic outcomes in association with microvascular injuries [ 71 ]. Endothelial injury, either due to virus invasion or in the context of profound inflammation increased levels of coagulation factors, hypoxia, due to respiratory impairment or anti-platelel factor 4 (PF4)-immune complexes, has been implicated in acute COVID-19 pathogenesis, predisposing to coagulopathy and thromboembolic complications in large blood vessels and microcirculation [ 53 , 72 , 73 ]. Thromboembolism may also complicate the post-COVID period in the context of a hypercoagulate state [ 74 ].…”
Section: Pathogenesis Of Post-covid Syndromementioning
confidence: 99%
“…In addition, in a previously healthy 56-year-old man with persistent neurological disorders, including short-duration epileptic seizures, and deep depression almost six months after COVID-19, CNS MRI revealed numerous hyperintense focal areas in the periventricular and subcortical white matter and in semioval centers, compatible with gliotic outcomes in association with microvascular injuries [ 71 ]. Endothelial injury, either due to virus invasion or in the context of profound inflammation increased levels of coagulation factors, hypoxia, due to respiratory impairment or anti-platelel factor 4 (PF4)-immune complexes, has been implicated in acute COVID-19 pathogenesis, predisposing to coagulopathy and thromboembolic complications in large blood vessels and microcirculation [ 53 , 72 , 73 ]. Thromboembolism may also complicate the post-COVID period in the context of a hypercoagulate state [ 74 ].…”
Section: Pathogenesis Of Post-covid Syndromementioning
confidence: 99%
“…The hypothesis that a factor present in the serum of COVID-19 patients, and inhibiting platelet activation induced by anti-PF4 antibodies, was evaluated and not confirmed. [ 28 ] In addition, another report also showed that among COVID-19 patients, the rate of positive EIA is significantly higher than in the general population. [ 29 ]…”
Section: Introductionmentioning
confidence: 99%
“…Several other studies also detected increased PF4/H-reactive antibodies in COVID-19 patients in the context of heparin treatment and patients are suspected of developing "classical" HIT, i.e. heparin exposure-induced HIT [38][39][40][41][42] . A recent randomized trial reported that therapeutic dose of UFH and LMWH did not improve organ dysfunction in critically ill patients with COVID-19 43 .…”
Section: Discussionmentioning
confidence: 88%